KIDDING PATTERN OF ASSAM HILL GOAT (Indian Journal of Animal Production and Management, 2014)
Data pertaining to 418 parturitions of Assam Hill Goat maintained at the adopted villages of AICRP on Goat Improvement, Goat Research Station, Burnihat were analysed to study the kidding pattern. The kidding was found to be distributed throughout the year with the highest kidding in the post-monsoon season (31.34%). Month-wise kidding records reveals that the highest and the lowest number of kidding was in the month of September (20.09%) and November (0.95%) respectively. The diurnal variation of spontaneous live births showed uni-model distribution with maximum kidding between 0600 to 1200 hours (56.46%) whereas the lowest incidence of kidding was recorded between 0.00 to 0600 hours. The percentage of single, twin and triplets were 60.76, 34.93 and 4.31 respectively. In the present study the percentage of male kid born was 50.50 per cent. The average birth weight of the male kids (1282.37gm) was higher than that of the female kids (1231.78 gm) at all types of birth (single, twins and triplets). The difference in birth weight between the sexes was non-significant. In rural Assam, goat plays an important role in the farming system as evidenced by the higher annual growth rate (9.66 %) during the census year 2003-20078 in comparison to all India Annual Growth Rate per cent of 3.10.
Keywords: Assam Hill Goat; kidding pattern; diurnal variation